Electrocatalytic Synthesis of gem-Bisarylthio Enamines and α-Phenylthio Ketones via a Radical Process under Mild Conditions - Pan, Yong-Zhou; Cheng, Shi-Yan; Li, Qian-Yu; Tang, Hai-Tao; Pan, Ying-Ming; Meng, Xiu-Jin; Mo, Zu-Yu (Synlett, 2021)
The novel method for the synthesis of gem-bisarylthio enamines and α-phenylthio ketones was developed via the coupling of α-substituted vinyl azides with thiols in the presence of tetrabutylammonium iodide (TBAI) as a redox catalyst and electrolyte at room temperature. Electronic properties were crucial in the generated products. This protocol features metal- and oxidant-free materials, broad tolerance of substrates, and mild reaction conditions.
Keywords: electrocatalytic; vinyl azides; thiophenols; gem-bisarylthio enamines; metal-free